Roll of the saliva like biological marker in buccal pathology. - Taboada Vega, Manuel E. (2006)
The XXI century characterized by technological noteworthy events in all disciplines of the human been. Concerning to the problematic health undoubtedly with the genetic code decipher (decade 50) and lastly with the sequence of the human genome (aims of the last century). This event comprise, also of medicine and on yours of oral cavity y bait of saliva county in what studies bases in results, shortly past will form the strategies of preparation in the diagnostic of treatment plan of the illness in hospitals and private practice convencionals of biologicals markers, genetics, test, genetics counsul; structure of this manner in news paradigms of future treatment for f illness of the oral cavity.